Litigating Reproductive Health Rights in the Inter-American System: What Does a Winning Case Look Like? - O'Connell, Ciara (My University, 2014)
Remedies and reparation measures emerging from the Inter-American System of Human Rights in reproductive health cases have consistently highlighted the need to develop, and subsequently implement, non-repetition remedies that protect, promote, and fulfill women’s reproductive health rights. Litigation outcomes that determine there have been violations of reproductive rights are regarded as a “win” for health rights litigation, but when implementation fails, is a “win” still a win? There has been considerable success in litigating reproductive health rights cases, yet the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights are not adequately equipped to follow up on cases after they have been won. Successful and sustainable implementation of reproductive health rights law requires incorporation of non-repetition remedies in the form of legislation, education, and training that seeks to remodel existing social and cultural practices that hinder women’s enjoyment of their reproductive rights. In order for a reproductive health rights case to ultimately be a “winner,” case recommendations and decisions emerging from the Commission and Court must incorporate perspectives from members of civil society, with the ultimate goal being to develop measurable remedies that address underlying obstacles to domestic implementation.
PUBLISHED
Keywords: Reproductive rights; Inter-American Human Rights system; Health rights; Women's rights; Inclusive Society; Gender Equality; Global Health; Reproductive health; WOMEN'S HEALTH